Analysis of Polymorphisms in the Lactotransferrin Gene Promoter and Dental Caries. (8th December 2011) - Brancher, João Armando; Pecharki, Giovana Daniela; Doetzer, Andrea Duarte; Medeiros, Kamilla Gabriella dos Santos; Cordeiro Júnior, Carlos Alberto; Sotomaior, Vanessa Santos; Bauer, Peter; Trevilatto, Paula Cristina
Abstract : Regarding host aspects, there has been strong evidence for a genetic component in the etiology of caries. The salivary protein lactotransferrin (LTF) exhibits antibacterial activity, but there is no study investigating the association of polymorphisms in the promoter region of LTF gene with caries. The objective of this study was firstly to search the promoter region of the human LTF gene for variations and, if existent, to investigate the association of the identified polymorphisms with dental caries in 12-year-old students. From 687 unrelated, 12-year-old, both sex students, 50 individuals were selected and divided into two groups of extreme phenotypes according to caries experience: 25 students without (DMFT = 0) and 25 with caries experience (DMFT ≥ 4). The selection of individuals with extreme phenotypes augments the chances to find gene variations which could be associated with such phenotypes. LTF gene-putative promoter region (+39 to −1143) of the selected 50 individuals was analyzed by high-resolution melting technique. Fifteen students, 8 without (DMFT = 0) and 7 with caries experience (mean DMFT = 6.28), presented deviations of the pattern curve suggestive of gene variations and were sequenced. However, no polymorphisms were identified in the putative promoter region of the LTF gene.